Penerapan Model Direct Instruction pada Pembelajaran Fisika - Aantri Heriyanti; Ovilia Putri Utami Gumay (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
This study aims to determine the completeness of physics learning outcomes class VIII SMP Ar-Risalah Lubuklinggau academic year 2017/2018 after applied Direct Instruction model. The type of research is quasi-experimental research, with the design used is one group pretest and posttest design. The population in this study is all students of class VIII SMP Ar-Risalah Lubuklinggau academic year 2017/2018. The sample of the study consisted of one class taken at random by drawing the class VIII.B. Technique of data collecting using technique of test. Student test score data were analyzed using t-test. Based on the results of the analysis of the final test data obtained t count = 2.84 greater than ttable = 1.703 with the average score of the final test of students amounted to 73.89 and the percentage of complete students reached 82.14%. So it can be concluded that the results of physics learning class VIII SMP Ar-Risalah Lubuklinggau academic year 2017/2018 after the implementation of Direct Instruction model significantly completed. Keywords: Direct Instruction Model, Learning Outcomes, Physics.